The global power of the purse - how women are leading the way in the 21st century economy - Warner, Fara (Henry Stewart Talks, 2009)
The economic impact of women globally, Perspectives on the women's economic power in countries such as India and China, How to reach women through marketing and advertising focused on their economic power